Is hypertension in African-descent populations contributed to by an imbalance in the activities of the ACE2/Ang-(1-7)/Mas and the ACE/Ang II/AT1 axes?. (February 2020) - Cohall, Damian; Ojeh, Nkemcho; Ferrario, Carlos M; Adams, O Peter; Nunez-Smith, Marcella
Introduction: Low plasma renin activity hypertension is prevalent in Afro-Caribbean persons. Reduced angiotensin converting enzyme 2 activity from the counter angiotensin converting enzyme 2 /angiotensin-(1-7)/Mas receptor axis of the renin angiotensin aldosterone system has been reported in people with pre-hypertension, type 2 diabetes mellitus and chronic renal disease. This study investigates whether an imbalance in the regulatory mechanisms between the pressor arm of the renin angiotensin aldosterone system (angiotensin converting enzyme/angiotensin II/AT1 receptor) and the depressor axis (angiotensin converting enzyme 2/angiotensin-(1-7)/Mas receptor) predisposes persons of African descent to hypertension. Methods: In total, 30 normotensives and 30 recently diagnosed hypertensives aged 18–55 of Afro-Caribbean origin who are naïve to antihypertensive treatment will be recruited from public sector polyclinics in Barbados. Demographic and anthropometric data, clinical blood pressure readings, 24-hour urine collections and venous blood samples will be collected. Biological samples will be analysed for renin angiotensin aldosterone system peptide markers using radioimmunoassay. Conclusion: We describe the design, methods and rationale for the characterization of renin angiotensin aldosterone system mechanisms that may contribute to hypertension predisposition in persons of African descent. Our findings will characterize any imbalance in the counter axes of the renin angiotensin aldosterone system in hypertensive Afro-Caribbeans with a potential view of identifying novel approaches with the use of renin angiotensin aldosterone system and mineralocorticoid blockers to manage the condition.